Performance characterization of the alya fluid dynamics simulator - Camelo, Guilherme Antonio (2016)
This research presents results of a performance characterization and a tracing methodology used for Alya running with a fluid dynamics model. Alya is a robust physics simulator that runs in parallel and is capable of solving different physics in a coupled way. One problem faced by Alya is the irregular load between resources and time. Experiments are conducted in parallel using the MPI specification implemented by OpenMPI, and the application is traced using the tracing tools Extrae and ScoreP. The analysis of the trace provides information about the different performance patterns such as the communications among ranks, and the effective application load imbalance. To evaluate the load balance, percent imbalance metric is used, along with an analysis of the execution/- communication ratio per timestep. The goal of the characterization of Alya is to provide information about aspects of the application that affect the performance providing a possible path of improvement to developers of the application. The tracing methodology comprises the usage of different tracing tools to provide a way to reassure the results and create complementary experiments.